Revisiting the Rosenbrock numerical solutions of the reactor point kinetics equation with numerous examples - Yang Xue; Jevremović Tatjana (Nuclear Technology and Radiation Protection, 2009)
The fourth order Rosenbrock method with an automatic step size control feature was described and applied to solve the reactor point kinetics equations. A FORTRAN 90 program was developed to test the computational speed and algorithm accuracy. From the results of various benchmark tests with different types of reactivity insertions, the Rosenbrock method shows high accuracy, high efficiency and stable character of the solution.